Enforcement of competition law in CARICOM : perspectives on challenges to meeting regional and multilateral obligations - Beckford, Delroy S. (SELA CaracasVE, 2009)
Raises some issues that have implications for coherence between the competition law regimes at the multilateral level, in particularl the General Agreement on Trade in Services (GATS) obligations, and that existing at the regional level made operative through the existence of FTAs, specifically under the Revised Treaty of Chaguramas.